Strategy to control occupational risk for Hepatitis B: impact on the vaccination and seroconversion rates in dentistry students - NOGUEIRA,Daniela Nunes (2018)
ABSTRACT Objective: To describe the development of a dentistry school strategy in order to reduce the occupational risk related to hepatitis B. Methods: The academic registration documents of 242 students entering the institution between the years 2006 and 2013, were evaluated, among which were of copies of the updated vaccination cards and anti-HBs serologic testing. Demographic variables and others related to the vaccination status of hepatitis B and seroconversion were considered. Results: One hundred percent of the students were found to be vaccinated, and 87.2% had vaccination records of three doses. The results of anti-HBs tests proved seroconversion in 91.3% of the students. From 2011, the dental school was able to institutionalize the follow-up behavior of the students who had anti-HBs non-reactive. Of the twenty individuals whose serology was negative, nine students (45% of the total and all of the 2011-2013 class) were followed-up and repeated the basic vaccination and anti-HBs test; eight seroconverted and one was considered a non-responder, increasing the percentage of immune students to 95%. Eleven (55%) had other unregistered behavior or the documents analyzed showed no data on them. Conclusion: The procedure of following-up the registration in vaccination records required by the Biosafety Committee of the institution was shown to be effective in reducing the occupational risk of hepatitis B among the students.